Essays on consumer brand engagement - Lourenço, Carlos Eduardo (2016)
Despite the growing interest in the brand engagement concept there has been debate about its conceptual foundations. This doctoral thesis explores the nature of the consumer brand engagement (CBE) construct. In the first paper, CBE is assessed within the Expectancy Theory framework to explain and clarify the probable anticipated results of engaging with a brand, and outcomes are categorized into a first level (resulting from personal effort allocated to interact with a brand) and a second level (consequence of first level outcomes) and a novel CBE definition is formulated. A comprehensive brand engagement framework is proposed using the Boundary-Spanning Marketing Organization Theory (MOR) as a consumer-brand touch point framework. From the theoretical foundations of the cognitive, emotional and behavioral dimensions of CBE, fifteen theoretical propositions are developed to incorporate a multilateral perspective on the construct’s theoretical tenets. In the second paper, four studies are used to develop a consumer brand engagement scale. Study 1 (n=11) uses literature review and in-depth interviews with consumers to generate scale items. In Study 2, eight experts evaluate 144 items for face and content validity. In Study 3 data collected with undergraduate students (n=172) is submitted to both exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) to further item reduction. Three hundred and eighty-nine responses from a consumer panel are used on Study 4 to evaluate model fit, using Confirmatory factor analysis (CFA) and Structural Equation Modeling (SEM). The proposed scale confirms excellent validity and reliability levels. Finally, in the third paper, a consumer engagement scale from Vivek et al. (2014) is replicated (n=598) with customers in an auto show, and extends the construct measurement debate using an Item Response Theory (IRT) perspective. Although the data achieved fit on a Classical Test Theory (CTT) using CFA, a graded response model (GRM) identifies five items that have low levels of discriminating power and provides low levels of information. The IRT approach indicates a possible path to future methodological improvements to marketing scales in general, and to the consumer engagement scale in particular.